Effect of CO2 Flow Rate and Calcination Temperature on the Synthesis Nanosized Precipitated Calcium Carbonate - Nooririnah, Omar; Jeefferie, Abd Razak; Yuhazri, Yaakob; Toibah, Abd Rahim (2010)
The precipitated of calcium carbonate has attracted much attention because of its numerous applications in various areas of plastics, textiles, rubbers, adhesives, paints and wastewater treatment. Nanosized of Precipitated calcium carbonate (PCC) will enhance the properties and give better performance. PCC consists of relatively pure calcium carbonate compared to ground natural calcium carbonate. Its high purity and close controlled particle size and shape are making it the white filler of choice. Nanosized precipitated calcium carbonate particles were prepared using spraying method. The particles were prepared using three (3) different concentrations of Calcium Hydroxide, Ca(OH)2, three (3) CO2 flow rate and three (3) different calcinations temperature. The three (3) concentration of Calcium Hydroxide that been used are 25g/200ml, 25g/ 400ml and 25g/800ml and each of these initial solution sprayed at three (3) different CO2 flow rate, 5l/per-minute, 7l/per-minute and 10l/per-minute. Calcium Carbonate, CaCO3 powders were then calcined at three (3) different temperature, 1100°C,1200°C and 1300°C. TEM analysis showed a decreased in particle size from 110nm at initial solution of 25g/200ml to 40nm at low concentration of 25g/800ml due to the decrease of ionic strength of the Calcium Hydroxide, Ca(OH)2. Images from SEM showed morphology of the particles changed to spindle-like or prismatic when the ionic strength of the Calcium Hydroxide, Ca(OH)2 was increased. XRD showed that the phase of precipitated calcium carbonate changed from calcite Calcium Carbonate, CaCO3 to calcium hydroxide at low concentration of initial solution.